Correlation of AFM/SEM/EDS Images to Discriminate Several Nanoparticle Populations Mixed in Cosmetics. (May 2021) - Delvallée, A.; Oulalite, M.; Crouzier, L.; Ducourtieux, S.; Lambeng, N.; Amor, W.; Bouzakher Ghomrasni, N.; Feltin, N.; Viot, A.; Jamet, C.
Abstract : Abstract: This paper presents a proof of concept for the discrimination of several nanoparticle populations mixed in consumer products. The methodology proposes correlation of AFM, SEM, and EDS data to obtain structural and chemical information on each particle in a mixed population. To this end, emphasis is placed on sample preparation, imaging specifications for each instrument, and data correlation with adapted software.